S51 Impact of a local incentive scheme on implementation of NICE guidance on smoking cessation in secondary care and a smoke free hospital in an inner city teaching hospital setting. (December 2018) - Patel, IS; Woodhouse, A; Dale, S; Skwarek, D; Gibb, C
Abstract : Introduction: Senior NHS leaders and organisations such as RCP and ASH have recently placed increased emphasis on the need to identify and treat tobacco dependence in healthcare settings. We report on the feasibility and lessons learnt from developing a system wide approach to implementing NICE guidance on smoking cessation in secondary care in an inner London teaching hospital, and the impact of a 3 year local incentive scheme on this. Method: King's College Hospital is a tertiary teaching hospital with 82 wards/1670 inpatient beds/12, 000 staff. A Smoke Free Strategy Group convened in 2013, led by BTS smoking cessation champion/consultant and involving key stakeholders. A 3 year local incentive scheme worth £2.5 million/year ran from 2014–2017 with incremental targets for recording smoking status, offering very brief advice and onward referral for inpatients plus staff training. An auditable electronic order was developed, linked to the National Referral System (NRS) for automated referral of smokers to their local service. 1 WTE hospital based tobacco liaison specialist was appointed in 2014 to support implementation and training. A Smoke Free Policy including smoke free grounds and inpatient nicotine withdrawal treatment algorithm were introduced in 2015. Results: Baseline data in 2013 showed that 40% of inpatients were current smokers and were highly tobacco dependent with 68% needing a cigarette within 30 min of waking. 64% wished to stop smoking and 77% expected help during their admission. Only 32% were offered NRT and 58% were given no information on smoking cessation. From 2014–2017 numbers of patients/year with smoking status recorded increased from 9770 to 16 231 to 22 101 and were 31 034 in 2017/18. Smoking prevalence ranged from 20%–25% with 90% smokers given very brief advice/offered treatment in year 1% and 76% in years 2/3. 34% smokers accepted smoking cessation referral in Year 1; 32% in year 2% and 21% in year 3. 62%, 45% and 57% respectively of these patients subsequently quit. 83% of nursing staff on inpatient wards completed appropriate training. Conclusion: System wide implementation of a smoke free hospital is challenging but feasible and successful. Financial incentivisation and clinical leadership are key facilitators.